Sejarah Penulisan dan Pembukuan Al-Qur’an - Randy Saputra amyus; Agustiar (Hikamatzu | Journal of Multidisciplinary, 2024)
The purpose of this research is to analyze the history of writing and codification of the Al-Quran. This study uses a qualitative approach to library research (library research). Sources of research data were obtained from books and journals related to Ulumul Qur'an. Data collection techniques by collecting literature data or library materials related to the discussion in the research. Data analysis was carried out by content analysis, namely content analysis which contains conclusions based on valid data by considering the context. The research concludes that the collection of the Al-Quran began during the time of the caliph Abu Bakr and continued with the codification of the Al-Quran during the time of the caliph Ustman bin Affan and in the third century of the Hijriyah there was a refinement of the rasm Utsmani, namely through the giving of signs and formulas. Among them are giving waqf signs, making juz signs, hizb signs, and other improvements.